Blended biomass pellets as fuel for small scale combustion appliances: Influence on gaseous and total particulate matter emissions and applicability of fuel indices. (15th November 2016) - Zeng, T.; Weller, N.; Pollex, A.; Lenz, V.
Highlights: Blending of wheat straw, miscanthus and pine wood was employed to highlight the emission reduction potential of this strategy for small scale combustion appliances. Applicability of several fuel indices was confirmed for blended fuels. A good correlation was found for the potassium content and the total particulate emission levels. Abstract: Non-woody biomass fuels have a great potential to replace fossil fuels and reduce greenhouse gas emissions. At the same time, their application in small scale combustion appliances for heat production is often associated with increased operational problems (e.g. slagging in the bottom ash or fouling) as well as elevated particulate and gaseous emission levels. To mitigate these problems, scope and limitation of blending raw materials owing critical fuel composition with less problematic biomasses have been systematically studied during combustion experiments in a commercially available small scale combustion appliance with a nominal heat capacity of 30 kW. Three pellet batches of pure biomass (i.e. pine wood, miscanthus and wheat straw) as well as seven blended biomass pellet batches have been employed. Slagging, emission of total particulate matter (TPM) and gaseous emissions (i.e. CO, NOx, SO2 and HCl) were monitored. The results were evaluated with respect to the emission reduction potential of the blending strategy as well as the applicability of fuel indices which were originally developed for coal and pure biomass fuels. Based on the results, blending of herbaceous raw materials with woody biomass reduces the slagging risk in the bottom ash and leads to reduced emission levels, though significant reduction potential was observed only for blends with at least 50 wt% wood. The blending of miscanthus with wood seemed to be more effective. Most of the fuel indices which were deduced from the chemical composition of the fuel seem to be applicable for a preliminary evaluation of blended biomass fuels and the prediction of critical emission levels.